Pertussis seroprevalence in adults, post-partum women and umbilical cord blood - Fallo, Aurelia A (2014)
Fil: Fallo, Aurelia. Hospital de Niños Ricardo Gutiérrez. Servicio de Infectología, Ciudad Autónoma de Buenos Aires; Argentina.